THERAPEUTIC PHYSICAL CULTURE IN NEUROCIRCULATORY DYSTONIA - Ass Usmanova Yayraxon G‘ulomovna (Web of Journals Publishing, 2025)
Disorders of external respiratory function, vascular tone, and thermoregulation are known to be driven by dysfunction of the nervous and humoral systems in patients with neurocirculatory dystonia (NCD).